Evaluation of the Implementation of Digital-Based Academic Administration in the Society 5.0 Era - Wahyu Fitriana, Fevi; Mulyadi, Edi; Hardian, Dafyar Eliadi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation of a digital-based academic administration system in higher education institutions within the context of Society 5.0. Using a qualitative approach with a case study method, this study collected data through in-depth interviews with 15 stakeholders, participant observation, and document analysis. The results showed that the digitalization of academic administration successfully increased process efficiency by 40% and reduced data input errors by 75%. However, the implementation of this system faced significant challenges in the form of resistance to change from users (especially senior staff), a digital competency gap, and interoperability issues with legacy systems. Key findings of the study revealed that the success of digital transformation depends not only on the technological aspect but also on a human-centered approach in system design and adoption processes. Institutions that implemented tiered training programs, technical assistance, and intuitive interfaces demonstrated a 30% higher implementation success rate. This study enriches the Technology Acceptance Model (TAM) by adding the dimension of psychological readiness as a critical factor in technology acceptance. The practical implications of this study emphasize the importance of a holistic approach that combines technological innovation with human resource capacity development. The study recommends the need for user-centric system design, responsive feedback mechanisms, and ongoing evaluation to ensure the sustainability of digital transformation. The limitations of this local study open up opportunities for further research with broader scope and longer observation periods. The findings of this study provide an important contribution to the development of digital transformation policies in higher education that align with the principles of Society 5.0.